ASEAN-5 Exchange Rate Determination In The Presence Of Nonlinearity - Venus Liew, Khim Sen; Ahmad Zubaidi, Baharumshah; Muzafar Shah, Habibullah; Habshah, Midi (Serials Publications, 2011)
This study finds that nominal exchange rate exhibits nonlinear long-run relationship with money supplies and aggregate outputs, in the context of ASEAN-5 countries, thereby validating the monetary model of exchange rate. While it is consistent with the earlier findings using the linear testing procedures in this region, the current evidence of nonlinear relationship provides insightful information in explaining why nominal exchange rate misalignments can sometimes be persistent in the short-run. With regard to the monitoring of exchange rates in these countries, policy makers could focus on the set of monetary variables, which have been shown well-coordinated with the dynamic of exchange rates in this study.